2012
DOI: 10.4314/bajopas.v4i2.6
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Major Ethno Medicinal Plants of Kano North, Nigeria, Their Knowledge and Uses by Traditional Healers

Abstract: An ethno botanical survey of major ethnomedicinal plants was carried out in the study area (Kano north senatorial district, Nigeria), their knowledge and uses by the local healers was determined. Data was obtained through the use of interviewer administered questionnaires, distributed at random to the traditional healers as the target respondents. Research shows that various plant species from 25 families were reported to be used in the treatment of various human ailments. Majority of these plants (73.2%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…Salmonella enterica typhi, is an obligate parasite which leads to the development of typhoid fever [18]. In previous studies, Leptadenia hastata has been reported to play an important role in growth inhibition against bacteria, fungi, viruses, hypertension and tumors [19][20][21][22]. In agreement with the report of Alero and Wara [23] that Methanol and water extracts from the leaves of Leptadenia hastata showed antibacterial activities.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Salmonella enterica typhi, is an obligate parasite which leads to the development of typhoid fever [18]. In previous studies, Leptadenia hastata has been reported to play an important role in growth inhibition against bacteria, fungi, viruses, hypertension and tumors [19][20][21][22]. In agreement with the report of Alero and Wara [23] that Methanol and water extracts from the leaves of Leptadenia hastata showed antibacterial activities.…”
Section: Discussionsupporting
confidence: 70%
“…Local healers also use the plant for hypertension, catarrh and skin diseases [11]. It is commonly used as a vegetable and is considered as a famine food in Niger republic due to its high content of valuable nutrients rich in various types of amino acids, fatty acids, terpenes, carotenes, luteines and poly-oxy pregnane [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some organs (stem bark, root bark and roots) possess anti-venomous activity according to some respondents. The anti-venomous activity of the plant was also reported by Dambatta et al (2011) in Nigeria. From the results of our survey, it also appears that the leaves and roots of this plant were used in the treatment of malaria, sexual impotence, cough, abscess, icterus and rheumatism.…”
Section: Discussionsupporting
confidence: 53%
“…Farmers deliberately grow the species in their homes as food readily available [10]. Local healers use the plant for hypertension, catarrh and skin diseases [11]. The breeders commonly used the leaf and the stems for the treatment of parasites and against placental retention among their animals [12,13].…”
Section: Introductionmentioning
confidence: 99%